Sistem Pemilihan Guru Terbaik Menggunakan Metode Moora Pada SMP Al-Wasliyah 9 Medan - Parulian Sinaga, Dedi Candro; Tampubolon, Gunung Juanda; Ndruru, Ifanlius (Jurnal Mahajana Informasi, 2022)
Al-Washliyah 9 Medan Private Middle School is a junior high school located in Belawan, Medan City, North Sumatra. Selection of the Best Teacher is a program initiated by Al-Washliyah 9 Private Middle School Medan to improve the quality and performance of teachers, which can affect professional allowances and promotions. A decision support system based on the Multi Objective Optimization by Ratio Analysis (MOORA) method was developed to assist in selecting the best teacher. The implementation of the MOORA method uses a decision support system as expected with a percentage of accuracy of the calculation on the test results of 100%. Applying the Multi-Objective Optimization by Ratio Analysis method or abbreviated as the MOORA method in determining the best teacher at SMP AL Wasliyah 9 Medan. The reason researchers use the MOORA method is because several previous researchers used a decision support system using the MOORA method in solving / resolving problems in decision makers. With research using this method, it is hoped that the school leaders/principals at SMP AL Wasliyah 9 Medan can minimize problems at school in determining the best teacher at school. So that when determining the best teacher is faster and more precise.